Eosinophilic Myocarditis: Differential Diagnosis on Endomyocardial Biopsy. Issue 3 (May 2021) - Jacobs, Jonathan; Burke, Allen
Abstract : Abstract: Eosinophilic myocarditis has multiple causes. When diagnosed on biopsy, sampling precludes diagnosing a specific cause in most cases. We report a case of presumed eosinophilic granulomatosis with polyangiitis diagnosed on endomyocardial biopsy and discuss the differential diagnosis.